Learning of general equilibrium effects and the unemployment trap - Gersbach, Hans; Schniewind, Achim (Discussion paper series, 2001)
We examine wage bargaining when employers and labor unions do not always take all general equilibrium effects into account but learn a steady state. If agents do hardly consider general equilibrium effects, low real wages and low unemployment results. With an intermediate view, when partial equilibrium effects are taken into account, high real wages and unemployment results, which may explain the persistence of high unemployment in Europe. If all general equilibrium effects are incorporated at once, again low real wages and low unemployment results. We thus obtain a hump-shaped relationship between the extend of feedback effects incorporated by the bargaining parties and real wages or unemployment.
Keywords: Graue Literatur; Arbeitspapier